Evolution of vibrational spectra in the manganese–silicon clusters Mn2Sin, n = 10, 12, and 13, and cationic [Mn2Si13]+ - Khanna, V; Singh, R; Claes, P; Nguyen, MT; Fielicke, A; Janssens, E; Lievens, P; McGrady, JE (American Chemical Society, 2022)
A comparison of DFT-computed and measured infrared spectra reveals the ground state structures of a series of gas-phase silicon clusters containing a common Mn2 unit. Mn2Si12 and [Mn2Si13]+ are both axially symmetric, allowing for a clean separation of the vibrational modes into parallel (a1) and perpendicular (e1) components. Information about the Mn–Mn and Mn–Si bonding can be extracted by tracing the evolution of these modes as the cluster increases in size. In [Mn2Si13]+, where the antiprismatic core is capped on both hexagonal faces, a relatively simple spectrum emerges that reflects a pseudo-D6d geometry. In cases where the cluster is more polar, either because there is no capping atom in the lower face (Mn2Si12) or the capping atom is present but displaced off the principal axis (Mn2Si13), the spectra include additional features derived from vibrational modes that are forbidden in the parent antiprism.